Ben Lappin's Reflections on May Day Celebrations in Toronto's Jewish Quarter - Tulchinsky, Gerald (Labour / Le Travail, 2002)
Tulchinsky introduces this reprint of "From the American scene: May Day in Toronto," by Ben Lappin. Originally published in Commentary in May 1955. Lappin's article portrays the annual May Day celebration of Toronto's working-class Jewish community at a time of generational transition.